The Influence of Service Quality on Patient Satisfaction in the Outpatient Installation - Wiguna, Paramita Kurnia; Hairat, Ummul; Latuconsina, Nur Aisah; Liklikwatil, ⁠Nelma; Losoiyo, Sylvianovelista R (GLOBAL HEALTH SCIENCE GROUP, 2024)
Hospitals provide services that are expected to satisfy and meet customer needs. Good service quality will maintain good relationships and create maximum satisfaction value. This study aims to determine the effect of service quality on patient satisfaction at the Rumkit Tk.II Dr. Outpatient Installation. J. A. Latumeten Ambon. The quantitative method uses a cross sectional design. The population of this study is all general patients who receive services. The sampling technique was carried out using stratified random sampling, proportional random sampling and using the formula from Lameshow to obtain 121 respondents. Data collection uses a questionnaire. The results in the research were that the majority of respondents were aged 25-35 years, female) and had at least a high school education. The majority of respondents visited internal medicine clinics where the distance between the respondent's house and the hospital was <5 km, the majority of whom had visited more than once. The results of the cross sectional test, the majority of respondents stated that the hospital was considered to have good service quality with a satisfaction level of 60 respondents (49.59%). The results of the analysis test obtained a p value = 0.000. So it was concluded that there was a statistically significant influence between the service quality variable and patient satisfaction at Rumkit Kindergarten. II Dr. J. A. Latumeten Ambon.